Factors Influencing Employee Retention: An Empirical study with Reference to IT Industry - V, Bhavani; kaur, Amanjot (The journal of contemporary issues in business and government, 2022)
Employee retention is one of the biggest challenges for HR in IT industry. It involves taking appropriate actions to motivate employees to stay in the company for long duration. The main focus of this study is to understand the factors which impact employee retention in software companies. For the study purpose sample of 7 software companies selected in Bangalore and structure questionnaire was prepared based various aspects of the software industry. An effort is made to discover the effectiveness of the retention of the employees in IT industry and how practical they are to retain employees for long duration. The results of this research study have shown that there is significance relationship between age, gender, years of experience with compensation & benefits.